(untitled) (Gloucester, UK, 1994)
This document presents the findings of the most comprehensive census ever carried out on Asian waterfowl. Over 3,000 wetlands in 32 countries were assessed; distribution maps for 200 commonly recorded species are presented, with the most important sites identified for each species; sites of international importance using the Ramsar 1% criterion are also identified. Some 496 wetlands were identified as being of international importance. A key conservation document for the region.
Keywords: Water birds,Chim